Institutional needs of the transgender student community at the University of the Witwatersrand - Mgolombane, Pura (My University, 2017)
Transgender students in higher education in South Africa are increasingly coming out. Though this coming out at huge to cost for them in terms of personal safety, alienation. potential harassment, bullying and discrimination, this group of students are insisting that campuses should be inclusive and safe for everyone irrespective of their gender, sexuality and/or sexual orientation. [Abbreviated Abstract. Open document to view full version]
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts in Diversity Studies, July 2017
Keywords: Transsexuals--South Africa--Interviews; Transgender people--South Africa; Gender identity--South Africa